(untitled) (MAUSAM, 1984)
pH data of monthly rainwater samples collected from 10 Background Air Pollution Monitoring Network stations in India alongwith the other published data regarding the precipitation chemistry and air pollution from different parts of India as well as from other parts of world have been studied for assessing the prospects of acid rain over India. It has been found that pH values over unpolluted areas in India may be between 6 and 7 and lowering of pH to acidic values (less than 5.6) might be restricted close to highly industrialized cities only such as Bombay (pH 4.5) and the phenomenon of acid rain may not be of regional nature. Main reason for the above is acid-base neutralization reactions in presence of basic particulate matter. Due to high level of suspended particulate matter over Agra of which & good fraction is expected to be of coarse mode, pH of rainwater over Agra is not expected to be. in the acidic range. It may also not change to acidic values after the commissioning of Mathura Refinery, since the expected increase in concentration of gaseous pollutants at Agra (specially SO2) is not large.